Injuries in the Chinese Arena Football League: American Versus Chinese Players - Chen, Tianwu (Orthop J Sports Med, 2018)
BACKGROUND: Arena football is an indoor version of American football played in indoor arenas on a smaller field with 8 players per team. Only 1 study has evaluated injury rates in arena football, and no study had compared 2 distinct cohorts of players. PURPOSE/HYPOTHESIS: The purpose of this study was to evaluate and compare injury rates in American versus Chinese athletes in the Chinese Arena Football League. Our hypothesis was that the rate of significant injuries (≥7 days of time lost from play) would be statistically significantly higher in Chinese athletes. STUDY DESIGN: Cohort study; Level of evidence, 2. METHODS: Each of the 6 teams included in this study comprised 11 American and 11 Chinese athletes, for a total of 132 included athletes (66 Chinese, 66 American). All players stayed in the same hotel, trained and played in the same facilities, and were covered by the same medical staff. A total of 18 games were played consecutively in 6 cities from October 1 to November 6, 2016. At least 4 Chinese players had to be on the field for each team at all times during game play. RESULTS: American athletes were significantly older, taller, and heavier than Chinese athletes. The total exposure was 759 athlete-hours, and there were 80 reported injuries, with 74 (92.5%) occurring during games (overall injury rate, 105.4 injuries per 1000 athlete-hours). For American athletes, the exposure was 387 athlete-hours with 38 injuries observed, and the injury rate was 98.2 injuries per 1000 athlete-hours. For Chinese athletes, the exposure was 372 athlete-hours with 42 injuries observed, and the injury rate was 112.9 injuries per 1000 athlete-hours. There was no statistically significant difference in exposure or overall injury rate between American and Chinese athletes. The rate of significant injuries was 30.3 per 1000 athlete-hours; there were 17 such injuries in Chinese athletes compared with 6 such injuries for American athletes. The rate of significant injuries was 45.7 (Chinese) and 15.5 (American) injuries per 1000 athlete-hours, and the relative risk for Chinese versus American athletes for significant injuries was 3.0 (95% CI, 1.2-7.8; P = .019) . Binary logistic regression models were utilized to analyze whether the baseline variables (height, weight, body mass index, age, years of experience, and nationality) were potential predictors for an injury, and only years of experience (odds ratio, 1.147 [95% CI, 1.034-1.271]; P = .009) was found to be associated with severe injuries (>21 days of time loss). CONCLUSION: The overall risk of injuries was similar between Chinese and American athletes, but Chinese athletes showed statistically higher rates of significant injuries than their American counterparts. Years of experience was the only factor that was associated with severe injuries. As professional sports become more global, medical personnel must take into account the distinct differences and levels of experience between the national and international professional athletes. The results of this study will be used to make recommendations to develop preventive training measures, including techniques to improve tackling.